'Guru' Culture in South Asia: The Case of Chinmaya Mission in India. (July 2016) - Pandya, Samta P.
Abstract: Guru culture is a prominent phenomenon in contemporary South Asia. The guru is a charismatic figure and the bedrock of the concerned institution, which very often assumes the form of a movement. Recognition of the power of that charisma is the central aspect in the social and psychological dynamics of guru-led movements. They attract a large number of followers and social service engagements are a part of their common repertoire, reflecting and furthering the guru's multiple societal entanglements. In this article, I focus on a prominent guru movement which originated in India, the Chinmaya Mission (CM), specifically with respect to its basic character and its interface with the Indian sociocultural fabric through compelling praxis, which I schematise through dimensions of its unique philosophical repertoire, sociality and habitus. Sociality in practice for CM is its mandate of social service. Social service is justified through the faith ideals. Habitus is generated by the Mission's associates as an unconscious formation. Both sociality and habitus of the CM movement make a case for the resurgence of religion and the postsecular in Indian public discourse.